Lenacapavir disrupts HIV-1 core integrity while stabilizing the capsid lattice - Chenglei Li; Ryan C. Burdick; Rokeya Siddiqui; Sanath Kumar Janaka; Ru-ching Hsia; Wei-Shau Hu; Vinay K. Pathak (Proceedings of the National Academy of Sciences, 2025)
Lenacapavir (GS-6207; LEN) is a potent HIV-1 capsid inhibitor approved for treating multidrug-resistant infection. LEN binds to a hydrophobic pocket between neighboring capsid (CA) proteins in hexamers and stabilizes the capsid lattice, but its effect on HIV-1 capsids is not fully understood. Here, we labeled HIV-1 capsids with green fluorescent protein fused to CA (GFP-CA) or a fluid-phase GFP content marker (cmGFP) to assess LEN’s impact on HIV-1 capsids. HIV-1 cores labeled with GFP-CA, but not cmGFP, could be immunostained with an anti-GFP antibody and were less sensitive to the capsid-binding host restriction factor MX2, demonstrating that GFP-CA is incorporated into the capsid lattice and is a marker for capsid lattice stability, whereas cmGFP is an indicator of core integrity. LEN treatment of isolated HIV-1 cores resulted in a dose-dependent loss of cmGFP signal while preserving the GFP-CA signal, indicating that LEN disrupts core integrity but stabilizes the capsid lattice. In contrast, capsid inhibitor PF-3450074 (PF74) induced loss of core integrity and the capsid lattice. Electron microscopy of LEN- or PF74-treated viral cores revealed frequent breakage at the narrow end of the capsid and other morphological changes. Our results suggest that LEN treatment does not prevent nuclear envelope docking but inhibits nuclear import of cores with or without loss of core integrity. In contrast, PF74 treatment blocks nuclear import by inhibiting the nuclear envelope docking of viral cores, highlighting their different mechanisms of nuclear import inhibition.